Syne2b/Nesprin-2 Is Required for Actin Organization and Epithelial Integrity During Epiboly Movement in Zebrafish - Li, Yu-Long; Cheng, Xiao-Ning; Lu, Tong; Shao, Ming; Shi, De-Li (Frontiers in Cell and Developmental Biology, 2021)
Syne2b/nesprin-2 is a giant protein implicated in tethering the nucleus to the cytoskeleton and plays an important role in maintaining cellular architecture. Epiboly is a conserved morphogenetic movement that involves extensive spreading and thinning of the epithelial blastoderm to shape the embryo and organize the three germ layers. Dynamic cytoskeletal organization is critical for this process, but how it is regulated remains elusive. Here we generated a zebrafish syne2b mutant line and analyzed the effects of impaired Syne2b function during early development. By CRISPR/Cas9-mediated genome editing, we obtained a large deletion in the sybe2b locus, resulting in truncation of the nuclear localization KASH domain in the predicted protein. Maternal and zygotic syne2b mutant embryos showed delayed epiboly initiation and progression without defect in embryonic patterning. Remarkably, disruption of Syne2b function severely impaired cytoskeletal organization across the embryo, leading to aberrant clustering of F-actin at multiple cell contact regions and abnormal cell shape changes. These caused disintegration of the epithelial blastoderm before the end of gastrulation in most severely affected embryos. Moreover, the localization and migration of yolk nuclear syncytium also became defective, likely due to disorganized actin networks at the blastoderm margin and in the yolk cell cortex. These findings demonstrate an essential function of Syne2b in maintaining cytoskeletal architecture and epithelial integrity during epiboly movement.